Oligogalacturonic Acid Inhibits Vascular Calcification by Two Mechanisms: Inhibition of Vascular Smooth Muscle Cell Osteogenic Conversion and Interaction With Collagen. Issue 7 (July 2017) - Hodroge, Ahmed; Trécherel, Eric; Cornu, Marjorie; Darwiche, Walaa; Mansour, Ali; Ait-Mohand, Katia; Verissimo, Thomas; Gomila, Cathy; Schembri, Carole; Da Nascimento, Sophie; Elboutachfaiti, Redouan; Boullier, Agnès; et al.
Abstract : Objective—: Cardiovascular diseases constitute the leading cause of mortality worldwide. Calcification of the vessel wall is associated with cardiovascular morbidity and mortality in patients having many diseases, including diabetes mellitus, atherosclerosis, and chronic kidney disease. Vascular calcification is actively regulated by inductive and inhibitory mechanisms (including vascular smooth muscle cell adaptation) and results from an active osteogenic process. During the calcification process, extracellular vesicles (also known as matrix vesicles) released by vascular smooth muscle cells interact with type I collagen and then act as nucleating foci for calcium crystallization. Our primary objective was to identify new, natural molecules that inhibit the vascular calcification process. Approach and Results—: We have found that oligogalacturonic acids (obtained by the acid hydrolysis of polygalacturonic acid) reduce in vitro inorganic phosphate–induced calcification of vascular smooth muscle cells by 80% and inorganic phosphate–induced calcification of isolated rat aortic rings by 50%. A specific oligogalacturonic acid with a degree of polymerization of 8 (DP8) was found to inhibit the expression of osteogenic markers and, thus, prevent the conversion of vascular smooth muscle cells into osteoblast-like cells. We also evidenced in biochemical and immunofluorescence assays a direct interaction between matrix vesicles and type I collagen via the GFOGER sequence (where single letter amino acid nomenclature is used, O=hydroxyproline) thought to be involved in interactions with several pairs of integrins. Conclusions—: DP8 inhibits vascular calcification development mainly by inhibition of osteogenic marker expression but also partly by masking the GFOGER sequence—thereby, preventing matrix vesicles from binding to type I collagen. Abstract : Supplemental Digital Content is available in the text.